Design for automated manufacture of composite structures - Astwood, Simon (Cranfield University, 2017)
New trends in manufacturing highlight the growing use of composite materials to produce lightweight, high performance structures. This requires the design stage to account for complex manufacturing constraints, and as industry begins to move towards automated manufacturing of composites, the more complex manufacturing constraints can introduce severe limitations to the design space, reducing the opportunity for designers to optimise a product. To address these limitations, this research proposes strategies for implementing design for manufacture specifically accounting for automated manufacture of composite structures. As a composite design develops, more detail is added, increasing the design fidelity. Typically design for manufacturing practices are only applied when the design fidelity is detailed enough to see individual plies. However, by implementing design for manufacturing practice at earlier stages of the design, when the design fidelity is low and design change is easy to implement, the greatest performance and manufacturing gains can be achieved. This research aims to develop a design process that uses digital technology to facilitate design for automated manufacture for composite structures. This research uses a systematic approach to create a generic design process and supporting tools, capable of identifying the key manufacturing constraints, and accounting for them at the earliest possible stages of the design. The proposed design process uses a strategy to apply design for manufacture using digital tools, and identifies actions required to enable automated composite manufacturing. The development of the design process is guided by the capture of the current industrial design practices. The proposed process is validated through the design and manufacture of an industrial demonstration structure, produced using an automated composite manufacturing process. The results from validation confirm the hypothesis that it is possible to have a generic design process to support the design for automated manufacturing of composites components.
Keywords: Design for manufacture; automated composite manufacture; automated deposition; DFM; FMEA; carbon fibre; design lifecycle